Forecasting Analysis of Cement Selling (Non-Bulk) Using The Method of Triple Exponential Smoothing (Case study: PT. Lafarge Holcim Cement Indonesia) - Zein, Ikramullah; Alsyah, Oloan; Apriliansyah, Surya (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2020)
PT. Lafarge Holcim Cement Indonesia is one of the cement companies focusing on construction. The aim of this study is to analyze the sales forecasting applied to know the next period using Triple Exponential Smoothing. The results showed that the values of MAD, MSE and MAPE for PCC's bag are 3980, 20925291 and 13%, respectively. Meanwhuile, the values for OPC's bag are 105, 19497 and 14%, respectively. Furthermore, the forcasting result of the next period of cement selling for PCC's and OPC's bag are 32498 and 792, respectively. Triple exponential smoothing method is a suitable method to forecast the case that has small bias, such as the case in PT. Lafarge Holcim Cement Indonesia.